Analysis of levels and Clinical value of CA19-9, NLR and SIRI in patients with Pancreatic Cancer with different Clinical Features - Min, Li; Ziyu, Dong; Xiaofei, Zhang; Shunhe, Xue; Bolin, Wang (Cellular and Molecular Biology, 2022)
This study aimed to investigate the levels of cancer antigen 19-9 (CA19-9), neutrophil/lymphocyte ratio (NLR) and systemic immune-inflammatory index (SIRI) in patients with pancreatic cancer with different clinical features and their clinical value. For this purpose, 78 patients with pancreatic cancer treated in our hospital from January 2018 to January 2021 were divided into two groups according to the NLR and SIRI calculated by blood routine and biochemical examination before operation. To observe and analyze the relationship between serum CA19-19 levels, clinical features and NLR and SIRI values in patients with different clinical stages and tumor diameter, and the diagnostic value of CA19-9, NLR and SIRI in pancreatic cancer. The results showed that the level of serum CA19-9 in patients with stage IV pancreatic cancer was significantly higher than that in patients with stage I, II and III, and the level of CA19-9 in patients with stage III was higher than that in patients with stage I and II, and the level of CA19-9 in patients with stage II was higher than that in patients with stage I. The level of CA19-9 in patients with pancreatic cancer with tumor diameter ≥ 5cm was significantly higher than that in patients with tumor diameter < 5cm. The percentage of patients with age ≤ 60 years old in high NLR group (83.78%) was significantly higher than that in low NLR group (63.41%), and the rate of patients with tumor diameter ≥ 5cm in the high SIRI group (54.05%) was significantly higher than that in low NLR group (26.83%). The rate of patients with tumor diameter ≥ 5cm in the high SIRI group (61.92%) was significantly higher than that in the low SIRI group (31.58%). Among the single indexes, the sensitivity of CA19-9 in the diagnosis of pancreatic cancer was the highest (93.10%). The specificity of Siri in the diagnosis of pancreatic cancer was 89.70%. The sensitivity and specificity of combined detection were 89.7% and 70.00%, respectively. In general, the level of serum CA19-9 in patients with pancreatic cancer increases gradually with the increase of clinical stage and tumor diameter. NLR value is related to patient age and tumor diameter, and SIRI value is related to tumor diameter. Combined detection of CA19-9, NLR and SIRI are of higher value in the early diagnosis of pancreatic cancer.